COVID-19 and fear of death: Has the pandemic changed our death orientation? - Rakesh Khanna (Wolters Kluwer -Medknow Publications, 2024)
The recent COVID-19 pandemic set the stage for a major upheaval. The entire world found itself caught in the specter of death. This review article outlines a case vignette of an orthopedic surgeon who was admitted to a COVID-19 ward at the height of the pandemic and was caught between an unfamiliar world of a doctor as a patient tormented by the likelihood of being the next casualty. The term coronaphobia has gained widespread currency. It has become a catch-all phrase for the fear and emotional and social strain experienced by people in the face of the COVID-19 pandemic. Death has been conceptualized in terms of (1) impersonal, (2) interpersonal, and (3) intrapersonal states. People were affected in all three ways. With nearly 7 million deaths even impersonal death mattered. Nearly everyone experienced the loss of one or more family and friends through the pandemic. Many who suffered from the illness had to face the prospect of personal death. As we move from the pandemic to the endemic stage of COVID-19, we must keep in mind the widespread untimely and catastrophic exposure to death. Many complex psychological challenges had to be faced. The lingering effect on people may be worth keeping an eye on. Adjustment disorder, posttraumatic stress disorder, exacerbation or relapse of preexisting conditions, and prolonged grief may be of concern.